Bisarylselanylbenzo‐2, 1, 3‐selenadiazoles: Synthesis, Photophysical, Electrochemical and Singlet‐Oxygen‐Generation Properties. Issue 46 (29th November 2018) - Balaguez, Renata A.; Krüger, Roberta; Iepsen, Bruna; Schumacher, Ricardo F.; Oliboni, Robson S.; Barcellos, Thiago; Junqueira, Helena C.; Baptista, Maurício S.; Iglesias, Bernardo A.; Alves, Diego
Abstract : We describe herein our results on the synthesis of bisarylselanylbenzo‐2, 1, 3‐selenadiazoles through double cross‐coupling reaction. The named compounds were obtained in moderate to good yields by reactions of a range of diaryl diselenides with the 4, 7‐dibromobenzo[ c ][1, 2, 5]selenadiazole using 20 mol‐% of CuO nanoparticles as a catalyst. In addition, the obtained compounds were investigated regarding their photophysical properties in solution and singlet oxygen generation. Bisarylselanylbenzo‐2, 1, 3‐selenadiazoles presents strong absorption bands at UV region and red emission properties, depending on the substituent. Geometrical, photophysical and electronic properties of the compounds are characterized with density functional theory calculations. In all derivatives are observed the oxidation process of Se atom, using electrochemical analysis. Also, the quantum yields of photosensitized 1 O2 production of the synthesized compounds were slightly lower than the standard, but still displays good ability to generate singlet oxygen species. The ability to generate 1 O2 of benzo‐2, 1, 3‐selenadiazole derivatives after being exposed to light and oxygen allowed us to envisage them as a potential application in photodynamic therapy. Abstract : The synthesis, photophysics, electrochemical and singlet‐oxygen‐generation properties of bis‐arylselanyl‐benzo‐2, 1, 3‐selenadiazoles are described. These compounds were obtained in moderate to good yields. The ability to generate 1 O2 of benzo‐2, 1, 3‐selenadiazole derivatives after exposure to light and oxygen allowed us to envisage them as a potential application in photodynamic therapy.